(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article devotes the origins of the recognition of customs as sources of law, their legal status and application in the Republic of Uzbekistan both at the legislative level, and provides an analysis from a theoretical point of view.